2019
DOI: 10.3390/ani9090649
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Owner-Reported Bacterial Infections in Pet Guinea Pigs

Abstract: Simple SummaryGuinea pigs are common pets but are susceptible to a range of diseases, some of which can be rapidly fatal without prompt veterinary attention. Bacterial infections are one cause of respiratory and gastrointestinal disease in guinea pigs, but few studies have reported how commonly these infections occur in pet guinea pigs or which types of bacterial infection are most often seen. A survey of guinea pig owners was conducted to assess the types of infections and signs of illness pet guinea pigs had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
2
Order By: Relevance
“…De las muestras de pulmón evaluadas, el 17.4% (24/138) resultó positivo a Streptococcus pneumoniae, este patógeno también se reporta en dos estudios a partir de diferentes órganos de cuyes (20), además ha sido asociada con neumonías en perros (21). Sin embargo, se ha identificado otras formas bacterianas concomitantes en los pulmones neumónicos evaluados, que han sido reportados en otros estudios, como Bordetella bronchiseptica, Streptococcus zooepidemicus, Klebsiella pneumoniae y Pasteurella multocida, debido a que se asocian como causa común de neumonía bacteriana en cuyes (4,5,13,22). Asimismo, se asoció Corynebacterium pseudotuberculosis en alpacas (10), Pasteurella sp, E. coli, Staphylococcus sp en cabras con neumonía (23).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De las muestras de pulmón evaluadas, el 17.4% (24/138) resultó positivo a Streptococcus pneumoniae, este patógeno también se reporta en dos estudios a partir de diferentes órganos de cuyes (20), además ha sido asociada con neumonías en perros (21). Sin embargo, se ha identificado otras formas bacterianas concomitantes en los pulmones neumónicos evaluados, que han sido reportados en otros estudios, como Bordetella bronchiseptica, Streptococcus zooepidemicus, Klebsiella pneumoniae y Pasteurella multocida, debido a que se asocian como causa común de neumonía bacteriana en cuyes (4,5,13,22). Asimismo, se asoció Corynebacterium pseudotuberculosis en alpacas (10), Pasteurella sp, E. coli, Staphylococcus sp en cabras con neumonía (23).…”
Section: Discussionunclassified
“…Los animales tienen microorganismos que constituyen la microbiota de diferentes tejidos, el Streptococcus pneumoniae forma parte del tracto respiratorio superior del cuy (5,12,13); sin embargo, también es considerado portador subclínico, pues ha sido reportado como patógeno en el tracto respiratorio superior con una prevalencia alta, con una frecuencia mayor al 50% en algunas poblaciones, esto explica las epizootias esporádicas que ocurren cuando los animales son estresados o desnutridos (4).…”
Section: Introductionunclassified
“…For example, dental disease, the most commonly diagnosed condition affecting guinea pigs, is believed to be often associated with poor diet 22 24 . A recent survey suggested that the occurrence of bacterial infections was unrelated to level of owner knowledge, 25 but did not test for associations with specific aspects of care. The authors’ survey asked about the occurrence of the most common diseases as reported in the literature, 10 21 22 and compared their occurrence with animal's housing and husbandry.…”
Section: Introductionmentioning
confidence: 99%
“…Research reveals its involvement in cases of lymphadenitis in Cusco, Peru with frequencies of 70 and 100 % in guinea pigs sampled with lesions [ 42 ]. However, other bacterial agents have also been identified, including Salmonella enterica serovar Typhimurium , Salmonella enteritidis , Staphylococcus aureus , Micrococcus spp, Streptococcus spp and Corynebacterium spp [ 43 ]. In addition to lymphadenitis S. equi subsp.…”
Section: Resultsmentioning
confidence: 99%